Co-expression network analysis of toxin-antitoxin loci in Mycobacterium tuberculosis reveals key modulators of cellular stress - Amita Gupta (Nature Portfolio, 2017)
Abstract Research on toxin-antitoxin loci (TA loci) is gaining impetus due to their ubiquitous presence in bacterial genomes and their observed roles in stress survival, persistence and drug tolerance. The present study investigates the expression profile of all the seventy-nine TA loci found in Mycobacterium tuberculosis. The bacterium was subjected to multiple stress conditions to identify key players of cellular stress response and elucidate a TA-coexpression network. This study provides direct experimental evidence for transcriptional activation of each of the seventy-nine TA loci following mycobacterial exposure to growth-limiting environments clearly establishing TA loci as stress-responsive modules in M. tuberculosis. TA locus activation was found to be stress-specific with multiple loci activated in a duration-based response to a particular stress. Conditions resulting in arrest of cellular translation led to greater up-regulation of TA genes suggesting that TA loci have a primary role in arresting translation in the cell. Our study identifed higBA2 and vapBC46 as key loci that were activated in all the conditions tested. Besides, relBE1, higBA3, vapBC35, vapBC22 and higBA1 were also upregulated in multpile stresses. Certain TA modules exhibited co-activation across multiple conditions suggestive of a common regulatory mechanism.